Using ESN-Smartphone Application to Maximize AIS Reperfusion Therapy in Alexandria Stroke Network: A Stroke Chain of Survival Organizational Model - Mansour, Ossama Yassin; Ramadan, Ismail; Elfatatry, Amer; Hamdi, Mohamed; Abudu, Ashraf; Hassan, Tamer; Eldeeb, Hany; Marouf, Hazem; Mogahed, Mohamed; Farouk, Mohamed; Abas, Mohamed; Hamed, Mervat; et al. (Frontiers in Neurology, 2021)
Abstract Background: In developing countries like Egypt, the clinical workflow of stroke management is poorly established due to the lack of awareness of the stroke patients concerning their need of therapeutic intervention and the poor identification of facilities equipped to treat stroke. Hence, establishing a stroke system of care in developing countries that can efficiently and rapidly triage patients to the appropriate reperfusion therapy center is imperative to improving stroke management and outcomes. Aims: To evaluate a pilot experience in stroke hospital identification and expediting decision-making in AIS treatment through the Alexandria stroke network and Egyptian Stroke Network (ESN)-app. Methods: Between 2017 and 2019, seven hospitals registered themselves on the AS-Network as pilot hospitals. The ESN-application was used to detect stroke type, tele-connect stroke teams and hospitals, track triage of patients to equipped facility in real time, and streamline stroke workflow. The quality of and time required for stroke management were compared between 84 patients with acute ischemic stroke (AIS) whose treatment involved the ESN-app and 276 patients whose treatment did not. Results: During this pilot study, 360 AIS cases received reperfusion therapy, 84 of which were indicated by the ESN-app. The use of the application was associated with the significant drop in time metrics for the reperfusion AIS-patients (door-in-door-out time; 56±34 min vs 96±45 min, door-to-groin puncture time; 50±7 min vs 120±25 min, door-to-needle time; 55±12 min vs 78±16 min with p<0.0001). Its use was also associated with higher rates of excellent outcomes at the 90-day follow-up (without ESN-app vs with ESN-app, 67.9% vs 47.1%, p =0.001) but no difference in 90-day mortality or symptomatic intracerebral hemorrhage (without ESN-app vs with ESN-app, 9.5% vs 11.2% and 4.8% vs 5.1%, p > 0.05). Conclusion: Our pilot experience demonstrated that the use of the ESN-app expedited the stroke treatment workflow and facilitated tele-connection between registered stroke facilities . Additionally, its use might be associated with achieving higher rates of excellent outcomes at 90 days, where a Larger scale study is needed for more confirmation.